(untitled) (Abhat Journal, 2024)
This Study aims to Identify the role of Libyan Women in Promoting the rights and duties of Citizenship on a Sample of Women leaders in higher education institutions. To achieve this, the study adopted a descriptive analytical approach due to the suitability of this approach to the nature and objectives of the current study. An electronic questionnaire was designed and distributed to a sample. A random sample of women leaders at the level of Libyan universities, which amounted to (150) Women leaders. To answer the study’s questions, the arithmetic means, standard deviations, and grades were extracted. The study concluded with a number of results, the most important of which are: that Libyan women leaders have a positive role in promoting rights and duties. Citizenship, and that political obstacles were the biggest obstacles that hinder women leaders within higher education institutions in promoting the rights and duties of citizenship.